Pemanfaatan Media Sosial Sebagai Strategi Pemasaran Pada Umkm Minuman Linumite - Ririn Putri Anggraeni; Siti Ning Farida (Jurnal Nusantara Berbakti, 2023)
Real Work Lecture (KKN) is a special form of community service activities carried out by students. KKN is an intracurricular lecture activity in the form of community service carried out by students in an interdisciplinary and cross-sectoral manner. This activity aims to increase students' sense of sensitivity and social cognition and assist the development process. Social media is an important factor for business actors in product marketing. One of the efforts to market their products is by creating achievement accounts on social media or market places. In practice, when creating a profile, you need a logo as the characteristics of the business, the symbol or identity of the business actor. This service was carried out in Sukorejo Village, Sukorejo District, Blitar City. Our assistance target is the Limunite UMKM. The steps taken are creating social media and websites, creating social media content, website design, and providing assistance to MSMEs regarding the use of social media and websites